Comparative study of MALDI-TOF MS and VITEK 2 in bacteria identification - Guo, Ling; Ye, Liyan; Zhao, Qiang; Ma, Yanning; Yang, Jiyong; Luo, Yanping (Journal of Thoracic Disease, 2014)
Background: Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has recently been introduced in diagnostic microbiology laboratories for the identification of bacterial and yeast strains isolated from clinical samples. This study aimed to evaluate the accuracy of MALDI-TOF MS in clinical microbiology diagnosis by comparing it with commonly-used VITEK 2 or gene sequencing. Methods: The performances of MALDI-TOF MS and VITEK 2 were compared retrospectively for identifying routine isolates. Discrepancies were analyzed by gene sequencing analysis of the 16S genes. Results: For 1,025 isolates, classified as 55 species of 25 genera, 1,021 (99.60%) isolates were accurately identified at the genus level, and 957 (93.37%) isolates at the species level by using MALDI-TOF MS. A total of 949 (92.59%) isolates were completely matched by both methods. Both methods found 76 unmatched isolates among which one strain had no definite identification by MALDI-TOF MS and VITEK 2 respectively. However, MALDI-TOF MS made no errors at the genus level while VITEK 2 made 6 (0.58%) errors at the genus level. At the species level, the identification error rates for MALDI-TOF MS and VITEK 2 were 5.56% and 6.24%, respectively. Conclusions: With a lower identification error rate, MALDI-TOF MS has better performance than VITEK 2 in identifying bacteria found routinely in the clinical laboratory. It is a quick and cost-effective technique, and has the potential to replace conventional phenotype methods in identifying common bacterial isolates in clinical microbiology laboratories.